Pemberitaan Injil dengan Demonstrasi dan Kuasa Roh Kudus: Eksegesis 1 Korintus 2:4-7 dalam Perspektif Pentakostal - Sitanggang, Vernineto (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2025)
This article presents an in-depth analysis of the passage of 1 Corinthians 2:4-7 from a Pentecostal perspective to examine the essential role of the demonstration and power of the Holy Spirit in the preaching of the gospel. Through qualitative textual exegesis, it is found that the preaching of the Gospel is not an action centered on man but on God. The conclusion of the study shows that the preaching of the gospel by demonstration and the power of the Holy Spirit based on 1 Corinthians 2:4-7 from a Pentecostal perspective is: the preaching of the gospel by the wisdom of God not the wisdom of man, by the belief in the power of the Holy Spirit, who gives courage in the proclamation of the Gospel, and performs miracu-lous signs. The foundation of true faith must be laid in the real power of God, manifested through the work of the Holy Spirit, a principle that remains crucial to the mission of the Pentecostal.     Abstrak Artikel ini menyajikan analisis mendalam terhadap perikop 1 Korintus 2:4-7 dari perspektif Pentakostal untuk mengkaji peran esensial demonstrasi dan kuasa Roh Kudus dalam pemberitaan Injil. Dengan metode kualitatif melalui eksegesis teks, ditemukan bahwa pemberitaan Injil bukanlah sebuah tindakan yang berpusat pada manusia, melainkan pada Allah. Kesimpulan penelitian menunjukkan bahwa pemberitaan Injil dengan demonstrasi dan kuasa Roh Kudus berdasarkan 1 Korintus 2:4-7 dari perspektif Pentakostal adalah: pemberitaan Injil oleh hikmat Allah bukan hikmat manusia, oleh keyakinan akan kuasa Roh kudus, yang memberikan keberanian dalam proklamasi Injil, dan mengadakan tanda-tanda ajaib. Fondasi iman yang sejati harus diletakkan pada kuasa Allah yang nyata, yang dimanifestasikan melalui pekerjaan Roh Kudus, sebuah prinsip yang tetap krusial bagi misi kaum Pentakostal.